2019
DOI: 10.1002/fee.2143
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of nitrogen deposition in the world's urban areas: a global data synthesis

Abstract: Human activities have altered the global nitrogen (N) cycle, elevating rates of atmospheric N deposition up to tenfold above pre‐industrial levels, with consequences for ecosystem function and human health. To date, most N deposition studies have been carried out in rural areas; however, there has been a recent surge of N deposition studies conducted in urban ecosystems due to the increased recognition that humans are greatly altering the N cycle in these environments. We synthesized data from 174 publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 50 publications
3
49
0
Order By: Relevance
“…Over the past century, fossil-fuel burning and artificial fertilizer application have substantially increased the global nitrogen (N) deposition (Decina et al 2020;Galloway et al, 2008;IPCC, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past century, fossil-fuel burning and artificial fertilizer application have substantially increased the global nitrogen (N) deposition (Decina et al 2020;Galloway et al, 2008;IPCC, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, vehicle NH 3 emissions have been suggested to be a key driver of N deposition in urban and urban-affected regions (Fenn et al, 2018). However, relating urban NH 3 emission sources to spatiotemporal N deposition patterns can be challenging due to the variety of potential emission sources that exist in the urban atmosphere including stationary fossil fuel combustion, waste containers, sewerage systems, transport from agricultural areas, and vehicles (Decina et al, 2017(Decina et al, , 2020Gong et al, 2011;Hu et al, 2014;Meng et al, 2011;Saylor et al, 2010;Sun et al, 2014Sun et al, , 2017Sutton et al, 2000;Whitehead et al, 2007). The N stable isotopic composition (δ 15 N) of NH 3 could be a valuable observational constraint to track source contributions and validate model apportionments (Felix et al, 2013(Felix et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen deposition (deposition of nitrate (NO 3 − ) and ammonium (NH 4 + ) ions) increased by anthropogenic usage of excess nitrogen fertilizers and fossil fuels (Galloway et al 2004) is still a major environmental concern in global scale (Decina, Hutyra, and Templer 2019;Dentener et al 2006;Kanakidou et al 2016;Reay et al 2008), while reducing trends in nitrogen deposition are also observed in some areas of Europe and North America as a result of efforts to mitigate anthropogenic nitrogen oxide emissions (Gilliam et al 2019;Schwede et al 2018;Waldner et al 2014). Increased nitrogen deposition variously affects forest ecosystems by altering biodiversity, productivity, biogeochemical cycles, energy dynamics, and so on (Chiwa et al 2018;Groffman et al 2018;Janssens et al 2010;Jia et al 2020;Reay et al 2008;Zhang, Chen, and Ruan 2018).…”
Section: Introductionmentioning
confidence: 99%